FORAGE YIELD AND QUALITY OF SIMPLE AND COMPLEX GRASS-LEGUMES MIXTURES UNDER MEDITERRANEAN CONDITIONS - Carita, Teresa; Simões, Nuno; Carneiro, João Paulo; Bagulho, José Moreira e Ana Sofia (Emirates Journal of Food and Agriculture, 2017)
In the experiments conducted in 2013/2014 at the National Institute for Agricultural and Veterinary Research (INIAV) experimental station in Elvas - Portugal, the agronomic and forage quality traits of various species (Triticale (X Triticosecale wittmack), Oat (Avena sativa L.), Grasspea (Lathyrus sativus L.), Red vetchling (Lathyrus cicera L.). Hairy vetch (Vicia villosa, Roth), Common vetch (Vicia sativa L.) and Fiel pea (Pisum sativum L.)) in pure stands as well as in mixtures were evaluated. The objective was to identify interesting species or fodder mixture able to produce early interesting biomass, both in quantity and quality, for the periods when there is scarcity of pasture. A randomized complete block design with three replications was used in the experiment. The studied parameters were: dry matter yield, crude protein content, neutral detergent fiber content (NDF) and in vitro digestibility. Analysis of variance revealed highly significant differences (P < 0.05) among treatments for all agronomic and forage quality parameters. Lowest dry matter production was recorded in the combination on red vetchling in the first cut (133 kg ha-1) and with grasspea in the second cut (1266 kg ha-1), but these treatments are characterized by the highest values of protein contents (16-23%), the highest digestibility (66-81%) and the lowest NDF content (24-39%).